Mechanical standardization of semiconductor devices. General rules for the preparation of outline drawings of surface mounted semiconductor device packages. Measuring methods for package dimensions of small outline J-lead packages (SOJ) Part 6-20, (31st December 2010) - British Standards Institution,
No abstract available